Distributed coordination control strategy for multiple residential solar PV systems in distribution networks. (May 2020) - Cheng, Zhiping; Li, Zhongwen; Liang, Jing; Si, Jikai; Dong, Lianghui; Gao, Jinfeng
Highlights: Voltage variation caused by the PV can be mitigated without additional investment. Proposed strategy is fully distributed, which is flexible, scalable and robust. Voltage regulation and the reactive power dispatch can be achieved simultaneously. Abstract: Distributed rooftop PV generator systems have been increasing significantly in distribution networks. However, due to the intermittent nature of the PV power generation, it is challenging to handle the fast voltage variation of the distribution system through dispatching traditional low response speed devices such as load tap changers and capacitor banks. In this paper, a distributed hierarchical control strategy is proposed to deal with the voltage fluctuation issues through real-time regulating the injection or consumption reactive power of the fast response PV inverters. The proposed control strategy includes a primary droop control level and an agent-based distributed secondary control level. The droop-based primary level control can quickly regulate the voltage of PV inverter with locally measured information to overcome the fast voltage variation. The agent-based secondary level control can guarantee the average bus voltage restoration and proportionally reactive power sharing among the PV inverters through distributed communication between neighboring agents. With the proposed control strategy, both the average bus voltage restoration and proportionally reactive power sharing can be satisfied, which improves the stability of the distribution system. Furthermore, the proposed strategy is a fully distributed method that can distribute the computational and communication tasks among the local controllers through working in parallel, which is more flexible, scalable, and insusceptible to single-point failure.